Treatment of Industrial Wastewater and Household Waste Using Electrocoagulation Method with Aluminum Electrode - S. Suyanta; S. Sunarto; Susila Kristianingrum; Regina Tutik Padmaningrum; Derifasay Salsabilla; K. Karlinda (Universitas Negeri Yogyakarta, 2022)
The treatment of industrial wastewater and household waste using the electrocoagulation method with aluminum electrodes aims to determine the optimal time and voltage to reduce iron content, manganese content, and TDS from industrial wastewater and household waste. The method used in this study was the electrocoagulation method with aluminum electrodes. The object of this research was the reduction of iron content, manganese content and TDS of industrial wastewater and household waste. The optimization test of electric voltage and electrocoagulation time was carried out at variations of electric voltage of 5, 10, and 15 volts and time variations of 1, 3, 6, 9, and 12 hours. Then the samples were analyzed using Atomic Absorption Spectroscopy (AAS), pH meter and TDS meter. The results showed that the optimal time and voltage to reduce iron content, manganese content, and TDS of industrial wastewater and household waste was 12 hours and 15 volts. After the electrocoagulation process, the iron content was reduced by 95.37%, the manganese content was reduced by 100%, the TDS value was reduced by 43.66%, and the pH value increased by 26.73%.